Renewable energy adoption in third world countries. (18th October 2022) - Tabassum, Mujahid; Kashem, Saad Bin Abul; Siddique, Md. Bazlul Mobin; Afrouzi, Hadi Nabipour; Ponnan, Suresh; Sharif, Hafiz Zafar
Over the past decade, the global use of renewable energy sources for electricity generation has grown significantly. This rise in the use of renewable energy has mainly been driven by increased awareness of the effects of climate change and the need for a sustainable and cleaner future. Clean energy technologies are essential in reducing poverty, expanding rural development, and protecting health while encouraging sustainability and environmental quality. This research aims to analyse the current technologies being implemented in developed countries and find out the useable matching options for third world countries on lower cost and strong sustainability. Furthermore, a low-cost and sustainable model for a selected third world country is proposed, simulated in Simulink MALTAB to compare, and observe the output and efficiency.